TUMBUHAN OBAT DI PEKARANGAN RUMAH MASYARAKAT LAMBIRAH, ACEH BESAR - Ernilasari, Ernilasari; Rizky Ahadi; Mukarramah, Mukarramah; Falah, Najmul (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2025)
This research aims to obtain information about the species of plants used as medicines in the home gardens of the Lambirah community, Aceh Besar. The study was conducted in Lambirah Village in December 2024 using an exploratory survey method. Samples were determined by purposive sampling based on the availability of home garden land. Data collection was carried out through semi-structured interview techniques with predetermined respondents and direct observation of plant species used as medicine in home gardens. The research parameters included the plant species utilized and the plant parts used. Data were analyzed qualitatively and presented descriptively based on the results of interviews with respondents. The results showed that the Lambirah community still maintains traditional medicinal practices based on medicinal plants, comprising 45 species belonging to 30 families, inherited from generation to generation. The most commonly used plant parts in treatment are leaves, fruits, rhizomes, flowers, bulbs, stems, sap, and bark. Home gardens not only serve as green spaces or sources of kitchen ingredients but also function as living pharmacies that provide significant benefits for family health. Keywords : Medicinal plants; home garden; Lambirah